The effects on riding performance using active vs passive recovery during a simulated motocross race - Ollé Casanovas, Aleix (2017)
Aleix Ollé Casanovas. 2017. The effects on riding performance using active vs passive recovery during a simulated motocross race. University of Jyväskylä. 53p.